(untitled) - Ghosh, Swati R. (Washington, D.C., 2006)
This study analyzes the key issues and constraints - in terms of efficiency, access and safety and soundness - faced by East Asian countries in developing their financial markets which are at different stages of development, drawing on global experience. The study takes stock of the initiatives being undertaken at the regional level to foster greater financial integration as a means of deepening and diversifying financial markets, and on the policy issues that need to be addressed at the domestic level to deepen and diversify financial markets and to actually benefit from the actions that are being taken at the regional level.
Keywords: Finance,Financial institutions; East Asia,East Asia